PETROLOGI AMFIBOLIT KOMPLEK MELANGE CILETUH, SUKABUMI, JAWABARAT - -, Aton Patonah; -, Haryadi Permana (Bulletin of Scientific Contribution, 2010)
Amphibolite is part of Ciletuh mélange complex that was exposed together with serpentinite, harzburgite, dunite, gabro and basalt. The rock is dominated by amphibole and andesine and rarely can be observed quartz. At some locations, the rocks have changed to ampbibolite epidote (oligoclase + hornblende + actinolite + epidote + chlorite). The result of mineral paragenesis and measurement of pressure and temperature indicates that amphibolites was formed of 5 kbar – 6 kbar with temperature 640oC – 660oC. Meanwhile amphibolites epidote was formed of 4 kbar – 5 kbar with temperature 410oC – 455oC. Obtaining pressure and temperature from amphibolites is indicated as result of obduction and then it has retrograded metamorphism to amphibolites epidote because of accretion and uplifting at Upper Oligosen. The indication is characterized by actinolite changed to chlorite, albite and epidote have replaced andesine, and another indication is the rim of hornblende is replaced by actinolite.